Analysis Of The Results Of The Implementation Of The Curriculum Development Acceleration And Learning Assistance Program In Higher Education To Support Independent Independent Campus In Indonesia - Putra, Pradipta Hendrawan; Dikdik, Asep; Aedi, Nur; Nurdin, Didin (Universitas Dharma Wacana, 2024)
This study aims to describe the results of the implementation of the Higher Education Curriculum and Learning Acceleration Assistance Program Supporting Independent Independent Campus implemented by the Directorate of Learning and Student Affairs, Directorate General of Higher Education, Research, and Technology, Ministry of Education, Culture, Research, and Technology. This study uses a qualitative methodology with a descriptive approach using data collection techniques through surveys and documentation studies of program results that have been reported by program recipients to the Directorate of Learning and Student Affairs as the program implementer. The results of the study show that this assistance program greatly assists study programs in reorienting their curriculum to implement the Independent Learning-Independent Campus (MBKM) program independently through various collaborations carried out by related partners. Thanks to this assistance program, all study programs receiving assistance have curriculum documents that support the implementation of the MBKM program. The form of learning activities most often designed and implemented by recipients of assistance is internships/work practices, followed by student exchange activities and teaching in schools. This assistance program needs to be continuously developed every year to be able to accelerate the implementation of the MBKM program in higher education through curriculum development and independent implementation of the MBKM program